The Changes in the Personnel Management Practices in Russian Companies - Людмила Михайловна Чеглакова (Journal of Economic Sociology, 2010)
Basing on the ethnographical cases and analysis of the first documents and interviews the author of the paper demonstrates how the practices of personnel management do differ depending on the enterprise goals.